Acute behavioral crises in psychiatric inpatients with autism spectrum disorder (ASD): Recognition of concomitant medical or non-ASD psychiatric conditions predicts enhanced improvement. (March 2015) - Guinchat, Vincent; Cravero, Cora; Diaz, Lautaro; Périsse, Didier; Xavier, Jean; Amiet, Claire; Gourfinkel-An, Isabelle; Bodeau, Nicolas; Wachtel, Lee; Cohen, David; Consoli, Angèle
Highlights: Resistant acute situations associated with autism and/or ID can improve in inpatient neurobehavioral units with interdisciplinary collaboration. Common etiologies are organic causes, environmental causes, and non-ASD psychiatric conditions. Recognition of concomitant medical or non-ASD psychiatric conditions predicts enhanced improvement. Increased number of challenging behaviors may actually increase likelihood of treatment success supporting allocation of appropriate resources for this population. Abstract: During adolescence, some individuals with autism spectrum disorder (ASD) engage in severe challenging behaviors, such as aggression, self-injury, disruption, agitation and tantrums. We aimed to assess risk factors associated with very acute behavioral crises in adolescents with ASD admitted to a dedicated neurobehavioral unit. We included retrospectively in 2008 and 2009 29 adolescents and young adults with ASD hospitalized for severe challenging behaviors and proposed a guideline (Perisse et al., 2010) that we applied prospectively for 29 patients recruited for the same indications between 2010 and 2012. In total, 58 patients were admitted ( n = 70 hospitalizations, mean age = 15.66 (±4.07) years, 76% male). We systematically collected data describing socio-demographic characteristics, clinical variables (severity, presence of language, cognitive level), comorbid organic conditions, etiologic diagnosis of the episode, and treatments. We explored predictors of Global Assessment Functioning Scale (GAFS) score and duration of hospitalization at discharge. All but 2 patients exhibited severe autistic symptoms and intellectual disability (ID), and two-thirds had no functional verbal language. During the inpatient stay (mean = 84.3 (±94.9) days), patients doubled on average their GAFS scores (mean = 17.66 (±9.05) at admission vs. mean = 31.4 (±9.48) at discharge). Most common etiologies for acute behavioral crises were organic causes [ n = 20 (28%), including epilepsy: n = 10 (14%) and painful medical conditions: n = 10 (14%)], environmental causes [ n = 17 (25%) including lack of treatment: n = 11 (16%) and adjustment disorder: n = 6 (9%)], and non-ASD psychiatric condition [ n = 33 (48%) including catatonia: n = 5 (7%), major depressive episode: n = 6 (9%), bipolar disorder: n = 4 (6%), schizophrenia: n = 6 (9%), other/unknown diagnosis: n = 12 (17%)]. We found no influence of age, gender, socio-economic status, migration, level of ID, or history of seizure on improvement of GAFS score at discharge. Severity of autism at admission was the only negative predictor ( p < .001). Painful medical conditions ( p = .04), non-ASD psychiatric diagnoses ( p = .001), prior usage of specialized ASD care programs ( p = .004), functional language ( p = .007), as well as a higher number of challenging behaviors upon admission ( p = .001) were associated with higher GAFS scores at discharge. Clinical severity at admission, based on the number of challenging behaviors ( r = .35, p = .003) and GAFS score ( r = −.32, p = .008) was correlated with a longer inpatient stay. Longer hospitalization was however correlated ( r = .27, p = .03) with higher GAFS score at discharge even after adjustment for confounding factors. Challenging behaviors among adolescents with ASD may stem from diverse risk factors, including environmental problems, comorbid acute psychiatric conditions, or somatic illness such as epilepsy or acute pain. The management of these behavioral challenges requires a unified, multidisciplinary approach.